Understanding Child Grooming and Preventive Strategies: Perspectives of Primary School Teachers and Parents - Heri Saptadi Ismanto; Ellya Rakhmawati; Wawan Priyanto (Bulletin of Counseling and Psychotherapy, 2026)
Child grooming represents a growing challenge for child protection because it commonly occurs before sexual abuse and is often disguised as caring or supportive behaviour, making early recognition difficult. This study aimed to explore how primary school teachers and parents understand child grooming and perceive strategies for its prevention. A qualitative phenomenological design was adopted to capture participants' lived perspectives. 12 participants, including six teachers and six parents, were purposively selected. Child grooming is an increasing child protection concern because perpetrators often conceal abusive intentions through seemingly caring relationships. This study explored how primary school teachers and parents understand child grooming and the preventive strategies they consider effective in the Indonesian context. A qualitative phenomenological design was employed. Twelve participants were purposively recruited, comprising six primary school teachers responsible for pupils' welfare and six parents of primary school children. Data were collected through semi-structured interviews and analysed using thematic analysis. Participants understood grooming as a gradual process of psychological manipulation involving trust-building, emotional dependency, and the exploitation of children's developmental vulnerabilities. They identified age-appropriate sexuality education, body autonomy, self-protection skills, digital safety awareness, and school–family collaboration as key preventive strategies. The findings highlight the importance of strengthening adults' understanding of grooming to support early identification and prevention. This study contributes contextually relevant evidence for developing school- and family-based child safeguarding initiatives in Indonesia.